Parents’ knowledge, attitude and practice towards seasonal influenza vaccination in Riyadh region, Saudi Arabia - Kamel A Alenazi (Journal of Infection in Developing Countries)
Introduction: Parents’ knowledge and attitudes regarding influenza vaccine significantly determine whether or not their children will receive the vaccine. The objective of the present study was to evaluate the knowledge, attitude and practice among Saudi parents towards vaccinating their children against influenza.